The influence of standardisation and task load on team coordination patterns during anaesthesia inductions. Issue 2 (2nd April 2009) - Zala-Mezö, E; Wacker, J; Künzle, B; Brüesch, M; Grote, G
Abstract : Background: The use of different forms of coordination according to situational demands plays a crucial role in teams working in complex environments. This study aimed to describe patterns of coordinative actions (CAs) as they occur during anaesthesia induction and to analyse the influence of two crucial situational factors on these patterns, namely the amount of existing standards and the level of task load. Methods: 23 anaesthesia inductions were videotaped, and CAs of the anaesthesia teams were coded. The coding system distinguished between implicit and explicit coordination, coordination via leadership and heedful inter-relating as the individual effort to reach smooth coordination. Five phases within anaesthesia inductions were determined according to their level of standardisation and task load. Results: Overall, 67.7% of all CAs were rated as explicit CA and 32.3% as implicit CAs. When we considered the duration of those CAs, we found the reverse tendency (coordination was explicit 40% of the time and implicit 60% of the time). In highly standardised phases, we observed less explicit coordination, less leadership behaviour and less heedful interrelating compared with less standardised phases. In high-task-load phases, we observed more heedful interrelating than in low-task-load phases. Conclusions: The anaesthesia teams relied greatly on implicit coordination, which contrasts with findings indicating a performance benefit through explicit coordination in other work settings. Standardisation in the form of written departmental directives may have a supportive effect on coordination by partially substituting for other forms of coordination. The effect of high task load should be tested further in a simulator setting, where high task load can be induced in a more controlled fashion.